(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
This paper examines the influence of social media on the growth and success of small business owners in Nigeria. The paper anchored the opportunity based theory and evaluation theory, and also reviewed several literature on the subject matter, and it found out that social media enables companies to achieve a better understanding of customer needs in order to build and foster effective relationships. The foundation of any business is the customer, therefore social networking provides small businesses with multiple opportunities to build closer and more profitable relationships with customers. The findings reveal that social media plays a pivotal role in enhancing the visibility, reach, and competitiveness of small businesses in Nigeria. Findings also reveal that social media has pushed business towards E-commerce use, enabled business to communicate open and clear messages hence led to more creativity in advertising and personal selling when meeting customer’s needs. In conclusion, this paper highlights the profound influence of social media on the growth and success of small businesses in Nigeria. By harnessing the power of social media platforms, small businesses can amplify their reach, engage with customers, and drive sustainable growth. Policymakers, business support organizations, and entrepreneurs alike can benefit from understanding and harnessing the potential of social media in fostering economic development and entrepreneurship in Nigeria.